Physicochemical Properties and Antioxidant Activities of Luteolin-Phospholipid Complex - Zhengxiang Ning (Molecules, 2009)
luteolin and phospholipid complex was prepared to improve the lipophilic properties of luteolin. The physicochemical properties of the complex were analyzed by ultraviolet-visible spectrometry (UV), infrared spectrometry (IR), X-ray diffractometry (XRD) and differential scanning calorimetry (DSC). The results showed that luteolin and phospholipid in the complex were joined by non-covalent-bonds and did not form a new compound. It was found that the complex was an effective scavenger of DPPH radicals, with an IC50 value of 28.33 μg/mL. In the Rancimat antioxidant test using lard oil as substrate, the complex also showed the strong antioxidant activity.